2011
DOI: 10.1007/s00234-011-0981-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the fractional anisotropy (FA) value of peripheral nerves and clinical significance of the age-corrected FA value for evaluating polyneuropathies

Abstract: The age-corrected FA value of the peripheral nerves helps to differentiate between age-related peripheral nerve degeneration and polyneuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
3
18
2
Order By: Relevance
“…As in previous reports, 16,20,33 we found that FA decreases moderately with age (Pearson correlation coefficient, −0.38; P = 0.01). T2-weighted normalized signal, ADC, and AD did not correlate with age (P > 0.05).…”
Section: Effect Of Agesupporting
confidence: 72%
“…As in previous reports, 16,20,33 we found that FA decreases moderately with age (Pearson correlation coefficient, −0.38; P = 0.01). T2-weighted normalized signal, ADC, and AD did not correlate with age (P > 0.05).…”
Section: Effect Of Agesupporting
confidence: 72%
“…Interestingly, a similar relationship has been observed for diffusion metrics in nerve. 33 For MTR values of proximal nerve, additional data are needed to demonstrate whether such a relationship exists. Nevertheless, the effect of age (and BMI) on MTR was small in the current study; therefore, the observed differences are likely driven by pathologic rather than demographic factors.…”
Section: Resultsmentioning
confidence: 99%
“…First, our case series involved only healthy volunteers, and their age group was relatively young. Although changes in the FA of the peripheral nerves caused by ageing have been reported, 21 these changes may not be very important because of the bilateral symmetry of the FA for the IAN. However, further studies are needed to confirm such changes in the IAN.…”
Section: Discussionmentioning
confidence: 99%
“…According to several previous studies Dentomaxillofac Radiol, 45, 20160200 birpublications.org/dmfr DTI of the IAN using 3T MRI that evaluated DTI of the peripheral nerves, the FA of an injured nerve became significantly lower than that of the normal nerve. [19][20][21] Furthermore, the use of DTI parameters on the contralateral side as an internal control was recommended for the evaluation of unilateral peripheral neuropathy. 22 These studies strongly indicate that differences in the condition of the IAN, such as normal and damaged regions, can be evaluated by comparisons of the values between the right and left IANs at the same positions.…”
Section: Discussionmentioning
confidence: 99%